2021
DOI: 10.1002/mar.21444
|View full text |Cite
|
Sign up to set email alerts
|

Fright, attention, and joy while killing zombies in Virtual Reality: A psychophysiological analysis of VR user experience

Abstract: To date, research on the user experience of Virtual Reality (VR) games is sparse even though VR and immersive gaming experiences are emerging as a substantial consumer based within the videogame industry. Using facial electromyography and skin conductance response measurement, the current research presents the first psychophysiological evidence to show that: (1) VR games may heighten affective responses such as fear and arousal; (2) different levels of immersion in various gameplay modes may evoke higher affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
19
1
Order By: Relevance
“…While research on the effects of telepresence on cognitive performance have been mixed in result, previous research has consistently found a positive impact of telepresence on persuasive outcomes (Bender & Sung, 2021; Cowan et al, 2021; Tsai et al, 2020; Vishwakarma et al, 2020). Klein (2003) asked participants to explore different wine categories on a flat‐screen computer, using either full‐motion video introductions or text and picture introductions.…”
Section: The Effects Of Telepresence On Memory Attitudes and Behavioral Intentionmentioning
confidence: 99%
“…While research on the effects of telepresence on cognitive performance have been mixed in result, previous research has consistently found a positive impact of telepresence on persuasive outcomes (Bender & Sung, 2021; Cowan et al, 2021; Tsai et al, 2020; Vishwakarma et al, 2020). Klein (2003) asked participants to explore different wine categories on a flat‐screen computer, using either full‐motion video introductions or text and picture introductions.…”
Section: The Effects Of Telepresence On Memory Attitudes and Behavioral Intentionmentioning
confidence: 99%
“…Research on digital gaming has been evident in journals across various fields including science, business and humanities. A recent special issue from Psychology & Marketing on “Digital Gaming and Marketing” (Phau et al,) has published papers in the area of virtual reality games (Bender & Sung, 2021), gamification via mobile applications (Kunkel et al, 2021), gamers’ divergent behaviour (Sharma et al, 2021), game mechanics and serous games for sustainability (Whittaker et al, 2021), game streaming (Yoganathan et al, 2021), game experience (Wang & Hang, 2021), and AI powered avatar (Butt et al, 2021). While searching in the databases, we came across hundreds of journals that published papers on digital games.…”
Section: Publication Trendmentioning
confidence: 99%
“…VR combines kinetic, visual, and audio components in a digital three‐dimensional (3D) world (Kim et al, 2020) to create an immersive, engaging, and innovative computer‐generated atmosphere (Bernes & Pressey 2012; Bonetti et al, 2018). AR similarly refers to a technology that creates supplementary sensory information, such as objects, avatars, and sounds, as an overlay on the real‐world (Guttentag, 2010; Wedel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%